Incidence and Risk Factors Association for Ventilator Associated Pneumonia in Neontal Intensive Care Unit - Kumar, Naresh; Malhotra, Preeti; Kaur Bagga, Amanjeet; Kaur, Gagandeep (Journal of Nepal Paediatric Society, 2022)
Introduction: Ventilator Associated Pneumonia (VAP), the nosocomial pneumonia developing in mechanically ventilated patients after 48 hours of mechanical ventilation, is the second commonest nosocomial infection in the neonatal intensive care unit (NICU). VAP occurring within 96 hours of initiation of mechanical ventilation is termed as early VAP and later than that is known as late VAP. The aim of this study was to determine the incidence rate and risk factors of early and late ventilator associated pneumonia in NICU. Methods: The study was conducted from December 2015 to November 2017 in which 40 neonates were ventilated for more than 48 hours of which those who developed VAP as per CDC criteria were enrolled in the study. Birth weight, gestation age, reintubation if needed and number of days of ventilation were noted. Statistical associations were further evaluated between various parameters of VAP and time of development of VAP. Results: Incidence of Early VAP was 12.5% and that of Late VAP was 87.5%. 93.95% neonates who were reintubated developed VAP. Duration of mechanical ventilation and re-intubation were significantly associated with the time of development of VAP. Birth weight and gestation age were statistically insignificant factors in determining VAP. Conclusions: Re-intubation and duration of mechanical ventilation are a significant risk factor for development of late VAP. Gestation age and birth weight have been identified as additional risk factors. Early diagnosis is necessary for appropriate treatment and decreased hospital stay.